The Urgency and Strategic Role of Maqasid Shari'ah and Maslahah in Responding to The Legal and Economic Challenges of Muslim Business - Wiryanto, Fadhli Suko (Journal Of Middle East and Islamic Studies, 2023)
The study of maqashid shari'ah began to receive intensive attention after the Prophet's death, especially when the Companions were faced with new problems and social changes that had never occurred when the Prophet Muhammad was still alive. With the existence of social changes as a result of the demands of the times and the dynamics of society, thus demanding the creativity of the friends seriously to conduct a study of the maqashid shari'ah as an effort to make legal breakthroughs to anticipate social changes that occur. Maqashid shari'ah and maslahat have a very urgent and strategic role to be used as a knife of analysis in answering questions related to sharia challenges and their maslahah, both in the fields of law, business economics, and even politics, moreover everything is growing with the There are various problems that arise today, so all of them must be answered with maqashid sharia based on the Qur'an and hadith